Palma and González Prada. Chronicle of a distancing - Varillas Montenegro, Alberto (2020)
It is well known that during the last years of the 19th century, Ricardo Palma was the victim of harsh and continuous attacks coming from Manuel González Prada and his followers, members of the Círculo Literario. For more than a century, literature researchers of those years have rehearsed multiple interpretations to explain the reasons that inspired writers and journalists, preferably young ones, to attack the author of Peruvian Traditions with such fury. The present article proposes to discuss the issue from a generational perspective, which is not surprising, but it insists that the censurable level the insults reached was due to the presence of the political journalist and satirist Luis Enrique Márquez in Revista Social and Círculo Literario, who a dozen years earlier had fiercely attacked Palma in defense of the government of President Manuel Pardo.